Multivalent binding in platinum metal complexes - Ghosh, Biswa Nath; Justus Liebig University Giessen (My University, 2011)
In this doctoral thesis, iodotrimethylplatinum(IV) complexes of different pyridine and 2,2´ bipyridine ligands are investigated. The crystal structures of both the mononuclear and dinuclear pyridine complexes reveal an octahedral coordination around the platinum(IV) and a facial arrangement of the methyl groups. The crystal structure of the dinuclear complexes confirms that the iodide ligand acts as a bridging ligand that holds the two platinum metal ions together.The reaction of the mononuclear pyridine complexes with iodotrimethylplatinum(IV) in chloroform results in the formation of the corresponding dinuclear complexes (both cis and trans isomers) of pyridines. Although the pyridine substituents have no significant influence on the crystal structures of either the mononuclear or the dinuclear complexes, the equilibrium population of these complexes in solution depends largely on the electronic effect of the pyridine substituent as well as on the steric bulk of the pyridine substituent. Iodotrimethylplatinum(IV) on treatment with 2,2´-bipyridine and its derivatives gives mono-nuclear 2,2´-bipyridine complexes. The crystal structure of the bipyridine complexes confirms the fac-octahedral coordination of the trimethylplatinum moiety and the bidentate coordination of the 2,2´-bipyridines. Bond length comparison shows that Pt-N bond distances in bipyridine complexes are slightly shorter than in the corresponding pyridine complexes, reflecting the better pi-acceptor character of the 2,2´-bipyridines. In addition, the N-Pt-N bite angle in the bipyridine complexes is much lower than in the pyridine complexes. It was also observed that in the crystal packing of 4,4´-Dichloro-2,2´-bipyridine complex of iodotrimethylplatinum(IV), intermolecular non-covalent interaction between methyl hydrogen and chlorine atom leads to the formation of zig-zag chain structures, which are linked through weak pi-pi interactions to form two-dimensional layer structure.The reaction of iodotrimethylplatinum(IV) complexes of pyridines with the corresponding 2,2´-bipyridines lead to the substitution of ligands resulting in the formation of chelate bipyridine complexes. The equilibrium for these substitution reactions strongly favours the formation of chelate products. The formation of chelate complexes in solution at equilibrium depends largely on the electronic effect of the substituent as well as on the nature of the solvent.

In dieser Arbeit wurden Iodidotrimethylplatin(IV)-Komplexe mit verschiedenen Pyridin- und 2,2´-Bipyridin-Liganden untersucht. Die Kristallstrukturen von sowohl mononuklearen und dinuklearen Pyridin-Komplexen zeigen eine oktaedrische Koordination des Platin(IV) und eine faciale Anordnung der Methylgruppen. Die Kristallstrukturen von dinuklearen Komplexen bestätigen, dass der Iodid-Ligand als verbrückender Ligand, der zwei Platin-Ionen zusammenhält, dient.Die Reaktion von mononuklearen Pyridin Komplexen mit Iodidotrimethylplatin(IV) in Chloroform resultiert in der Bildung des entsprechenden dinuklearen Pyridinkomplexes (sowohl cis- als auch trans-Isomer). Obwohl die Pyridinsubstituenten keinen signifikanten Einfluss auf die Kristallstruktur sowohl von mononuklearen als auch von dinuklearen Komplexen haben, hängt das Gleichgewichtsverhältnis beider Spezies in Lösung zu einem großen Teil von den elektronischen Einflüssen der Substituenten, sowie deren sterischem Anspruch ab.Die Reaktion von Iodidotrimethylplatin(IV) mit 2,2´-Bipyridin und dessen Derivaten erzeugt mononukleare 2,2´-Bipyridin-Komplexe. Die Kristallstrukturen der Bipyridin-Komplexe bestätigen die fac-oktaedrische Koordination des Trimethylplatin-Rests und die bidentale Koordination der 2,2´-Bipyridine. Ein Vergleich der Bindungslängen zeigt, dass der Pt-N Bindungsabstand in Bipyridin-Komplexen leicht kürzer ist als in den entsprechenden Pyridin-Komplexen, was die besseren pi-Akzeptor Eigenschaften von 2,2´-Bipyridinen zeigt. Des Weiteren ist der N-Pt-N Winkel in Bipyridin-Komplexen wesentlich kleiner als in Pyridin-Komplexen. Zudem wurden in der Kristallpackung des 4,4´-Dichlorido-2,2´-bipyridin-Komplexes von Iodidotrimethylplatin(IV) intermolekulare, nicht kovalente Wechselwirkungen zwischen den Methyl-Wasserstoffatomen und den Chloratomen festgestellt, die zu der Ausbildung von kettenartigen Zick-Zack-Strukturen führen, die über schwache pi-pi-Wechselwirkungen verbunden sind und eine zweidimensionale Schichtstruktur erzeugen.Die Reaktion von Iodidotrimethylplatin(IV)-Pyridinkomplexen mit den entsprechenden 2,2´-Bipyridinen führt zu einer Substitution der Liganden, die in der Bildung von Chelat-Bipyridin-Komplexen resultiert. Im Gleichgewicht ist die Bildung des Chelatprodukts bei dieser Substitutionsreaktion stark bevorzugt. Die Bildung von Chelat-Komplexen in Lösung hängt im Gleichgewicht zu einem großen Teil von den elektronischen Effekten der Substituenten sowie von der Natur des Lösungsmittels ab.
Multivalente Bindungen in Platinmetallkomplexen
Keywords: ddc:540